Clinical implications of different specimen types for nucleic acid testing in two cases of COVID-19. Issue 8 (August 2020) - Fan, Hengwei; Yu, Xiaqing; Fu, Xiaohui; Zhu, Hengmei; Lv, Zhongwei; Yi, Wanwan; Zhang, Qian
The novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleic acid test is currently the gold standard for diagnosing coronavirus disease 2019 (COVID-19). This disease requires high-quality viral nucleic acid tests, and selecting the type of specimen from patients, who are at different disease stages, to use in the nucleic acid test is challenging. This article reports in detail the diagnosis and treatment process for two patients with confirmed COVID-19 and analyzes the results of the SARS-CoV-2 nucleic acid tests that were used for different types of specimens (sputum from deep cough, nasopharyngeal swab, and feces). The nucleic acid testing results of sputum from deep cough showed the best performance for positive detection. Our findings provide a reference for selecting the most suitable specimen for the clinical diagnosis of COVID-19 and improving the positive detection rate.